Correspondence bias of Chinese and American undergraduates: similar initial trait attributions but different situational corrections. Issue 2 (3rd April 2021) - Di, Meilin; Wang, Xiaoying; Zhao, Jingjing; Feng, Wei; Zhao, Jianbao; Nguyen, Kate; Wang, Yonghui
Abstract: Correspondence bias (CB) refers to individuals' tendency to make trait inferences regarding the constrained behavior of others. To investigate the influences of the attitude diagnosticity of behavior and situational constraints on CB in a cross-cultural context, a sample of 357 Chinese undergraduates (140 males, 39.2%) aged 17–27 years old ( M age  = 21.13, SD  = 1.94) and 252 American undergraduates (111 males, 44%) aged 16 to 24 years old ( M age  = 20.39, SD  = 1.70) took part in a modified attitude attribution task. The results of analysis of covariance showed that (a) Americans and Chinese undergraduates produced similar patterns in which CB decreased with the attitude diagnosticity of behavior, while (b) only Chinese undergraduates' CB decreased as situational constraints increased. These results indicated that the initial trait attributions were similar for individuals in America and China, but there were cultural differences in the stage with situational constraints.